tṣ‛h ḥdšh lzyhwyh šl “ktk” bktwbwt spyrh - Malamat, Abraham
A New Proposal for the Identification of KTK in the Sefire Inscriptions; Census Lists and Genealogies and their Historical Implications for the Times of David and Saul; KTK = Ki-[x]-qa in Shalmaneser III’s Kurkh Monolith, III R 7 i 31-33.